MENINGKATKAN KEMAMPUAN BAHASA EKSPRESIF ANAK USIA 4-5 TAHUN MELALUI KEGIATAN PEMBIASAAN PRESENTASI HASIL KARYA - Kusniati, Yuli; Sulaeman, Devi; Riyadi, Ahmad (Penerbit Lafadz Jaya, 2025)
The purpose of this study was to analyze the expressive language abilities of children aged 4–5 years through habituation activities of presenting their work at PAUD Melati III, Margakaya Village, Telukjambe Barat District, Karawang Regency. This classroom action research involved children aged 4–5 years as research subjects. Initial findings in the pre-cycle indicated that only 46% of children were able to use complex sentences, 50% could express feelings, 52% were able to recount personal experiences, and 54% could ask and answer questions appropriately. The intervention consisted of structured activities that encouraged children to routinely present their work in front of peers and teachers. Data were collected through observation, interviews with teachers and parents, as well as documentation. The results showed a significant improvement in children’s expressive language skills. The classical success rate increased from 50% in the pre-cycle to 65% in Cycle I, and continued to rise to 79% in Cycle II, surpassing the established performance indicators. In Cycle II, 23% of children reached the “Very Good” category, while 77% achieved the “Good” category, with no children categorized as “Poor.” These findings demonstrate that habituation to presentation activities effectively enhances expressive language skills in early childhood.